MAXIMUM PROFIT ANALYSIS USING LINEAR PROGRAMMING SIMPLEX METHOD AND POM-QM SOFTWARE AT UKM PIE BU SRI - Sudiantini, Dian; Santika, Elsa; Putri, Dhea Silvia; Amalia, Siti Nur; Affiyah, Nabella Nur (LPPM Institut Pendidikan Nusantara Global, 2024)
In current conditions, many people are competing to set up businesses to meet their daily living needs. One of the various ways to improve people's welfare is through small and medium enterprises (SMEs). As many businesses develop and are accompanied by intense competition, many problems will arise and will affect the profits of SMEs. The problem that occurs at UKM Pie Bu Sri is the problem of calculating the optimum profit obtained every day from the production of its activities. The aim of this research is to help calculate the optimum profit for UKM Pie Bu Sri so that it can be done accurately and quickly. In order to achieve this goal, the Simplex Linear Programming Method and QM for Windows Software were used to find the optimum profit estimate obtained in each production activity carried out by UKM Pie Bu Sri within a period of one day. The results of the maximization calculations show that in order to achieve maximum profits, Mrs. Sri must make 60 Brownie Pies and produce 25 Fruit Pies with a profit of IDR 99,500 per day.